Overexpression of miR-101 suppresses collagen synthesis by targeting EZH2 in hypertrophic scar fibroblasts. Issue 1 (26th November 2021) - Li, Jie; Li, Yan; Wang, Yunchuan; He, Xiang; Wang, Jing; Cai, Weixia; Jia, Yanhui; Xiao, Dan; Zhang, Jian; Zhao, Ming; Shen, Kuo; Li, Zichao; et al.
Abstract: Background: MicroRNA-101 (miR-101) is a tumor suppressor microRNA (miRNA) and its loss is associated with the occurrence and progression of various diseases. However, the biological function and target of miR-101 in the pathogenesis of hypertrophic scars (HS) remains unknown. Methods: We harvested HS and paired normal skin (NS) tissue samples from patients and cultured their fibroblasts (HSF and NSF, respectively). We used quantitative reverse transcriptase polymerase chain reaction (qRT-PCR), fluorescence in situ hybridization (FISH), enzyme-linked immunosorbent assays (ELISA) and Western blot analyses to measure mRNA levels and protein expression of miR-101, enhancer of zeste homolog 2 (EZH2), collagen 1 and 3 (Col1 and Col3) and α-smooth muscle actin (α-SMA) in different in vitro conditions. We also used RNA sequencing to evaluate the relevant signaling pathways and bioinformatics analysis and dual-luciferase reporter assays to predict miR-101 targets. We utilized a bleomycin-induced fibrosis mouse model in which we injected miR-101 mimics to evaluate collagen deposition in vivo . Results: We found low expression of miR-101 in HS and HSF compared to NS and NSF. Overexpressing miR-101 decreased Col1, Col3 and α-SMA expression in HSF. We detected high expression of EZH2 in HS and HSF. Knockdown of EZH2 decreased Col1, Col3 and α-SMA in HSF. Mechanistically, miR-101 targeted the 3′-untranslated region (3′UTR) of EZH2, as indicated by the decreased expression of EZH2. Overexpressing EZH2 rescued miR-101-induced collagen repression. MiR-101 mimics effectively suppressed collagen deposition in the bleomycin-induced fibrosis mouse model. Conclusions: Our data reveal that miR-101 targets EZH2 in HS collagen production, providing new insight into the pathological mechanisms underlying HS formation.